Use and perception of information sources on COVID-19 measures by citizens of Belgium - van Loenhout, Joris Adriaan Frank; Aujoulat, Isabelle; Van den Broucke, Stephan (Frontiers in Communication, 2022)
Background The effectiveness of adherence to COVID-19 infection prevention and control (IPC) measures depends on effective risk communication. This study assessed use and perception of COVID-19 information sources and channels in Belgium, and the relationship with adherence to measures. Methods Data were collected through an online questionnaire among a sample of 2008 respondents, representative for citizens of Belgium in terms of gender, age, socio-economic status, and region. Potential information sources named in the questionnaire were politicians, experts, journalists, and close contacts. Results Overall, experts contributed most to informing people on COVID-19 measures, and their information was considered clearest and most trustworthy, while politicians scored lowest for information clarity. All information channels were used by large proportions of respondents, namely television 80.2%, (online) newspapers 56.5%, radio 35.7% and social media 27.7%. Factors that contributed significantly to adherence in a multivariate model included use and perception of information from experts, which had a positive association, and relying on social media as an information channel, for which the relationship was negative. Conclusions It is important to achieve clear and trustworthy risk communication, as this contributes to overall adherence to IPC measures on COVID-19. Furthermore, attention should be given to the fact that for people who rely on social media as an information channel, their adherence can be adversely affected.